The Dream of the North A Cultural History to 1920 (Volume 23) - Fjågesund, Peter (Brill, 2014)
Northern Europe and North America have dominated the world stage for more than two centuries. Using a wide range of sources, this book provides the first coherent account from a multi-national perspective of the ideas and perceptions that, from the Renaissance onwards, fuelled the North's rise to prominence, and enabled it to rival the traditional cultural and political hegemony of the South. This includes not only the fascinating conquest of the polar regions, but also the religious upheaval of the Reformation, the changing view of nature engendered by Romanticism, and, not least, the revival of ancient Nordic and Celtic culture. Finally, the book offers an indispensable historical background to current events in the Far North, where the past and the future meet in a complex web of dramatic environmental concerns, the exploitation of natural resources, and the strategies of politics and commerce.